What are evidence-based treatment recommendations? - Barbui, C; Cipriani, A (2011)
In recent years new methodologies for developing treatment recommendations that give consideration to evidence, values, preferences and feasibility issues have been developed. One of the most well-developed approaches is the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. This article briefly presents how this methodology may be employed to develop treatment recommendations that might constitute a permanent infrastructure between primary research and everyday clinical practice.